Manifestation of Maslahah Mursalah in Public Transportation: An Analysis of The Socio-Economic Impact of Bus Trans Palu on Community Welfare - Nur Wanita; Idris Idris; Murniati Ruslan; Syaifullah MS (International Journal of Nusantara Islam, 2026)
Public transportation is a vital instrument for urban mobility and economic efficiency. In Palu, the government launched the Bus Trans Palu (BTP) service as mandated by Law No. 22 of 2009 to provide safe and inclusive transportation. From an Islamic Economic perspective, such provision serves as a form of government obligation to ensure the fulfillment of public needs (maslahah).This study aims to explore the socio-economic impacts of the Bus Trans Palu from the users' perspective, analyzed through the lens of Islamic Economics. This research utilizes a qualitative descriptive approach. Data were collected through in-depth interviews with 20 informants from diverse socio-economic backgrounds, including civil servants, students, and street vendors. The data were analyzed thematically and synthesized using Islamic economic principles, specifically Maslahah Mursalah (public interest) and Tawazun (balance). The results indicate that Bus Trans Palu provides significant social benefits by enhancing accessibility to education and work centers. It creates an egalitarian social space that fosters community interaction (ukhuwah). Economically, the service offers substantial cost efficiency, especially for low-income groups and students, allowing for household savings. Furthermore, the presence of bus stops has stimulated the real sector by creating opportunities for micro-entrepreneurs and informal traders.The implementation of Bus Trans Palu aligns with the concept of Maslahah Mursalah, as it reduces economic disparity through equitable access and supports sustainable urban living. This study recommends a single-fare integration system to further optimize economic justice for passengers requiring multiple transfers.